Efficacy of Diacetate Esters of Macular Carotenoids: Effect of Supplementation on Macular Pigment - Richard A. Bone; John T. Landrum; Anirbaan Mukherjee (Journal of Nutrition and Metabolism)
The accumulation of the carotenoids lutein, zeaxanthin, and mesozeaxanthin in the center of the human retina, and known as the macula lutea or macular pigment, is believed to protect the retina from age-related macular degeneration. Since the macular pigment is of dietary origin, supplements containing the relevant carotenoids are readily available. In this study, we compared the changes in macular pigment over a 24-week supplementation period for two groups of 24 subjects each assigned to either of two supplement formulations, 20 mg/day of lutein or 20 mg equivalent free carotenoids of a combination of diacetate esters of the macular carotenoids. The latter group responded with a larger increase (0.0666 ± 0.0481) in macular pigment optical density than the former group (0.0398 ± 0.0430), driven largely by the older subjects. The difference was statistically significant (p=0.0287). There was a general trend towards smaller increases in macular pigment for those subjects whose baseline value was high. However, the trend was only significant (p<0.05) for subjects in the diacetate group. No differences in response could be attributed to the gender of the subjects. We also observed no indication that the use of statin drugs by a few of the older subjects influenced their responses.